NAD-Dependent Protein Deacetylase Sirtuin-1 Mediated Mitophagy Regulates Early Brain Injury After Subarachnoid Hemorrhage - Wang G; Lin N (Dove Medical Press, 2024)
Gen Wang, Ning Lin Department of Neurosurgery, The Affiliated Chuzhou Hospital of Anhui Medical University (The First People's Hospital of Chuzhou), Chuzhou, Anhui Province, People's Republic of ChinaCorrespondence: Ning Lin, Email lin_neurosurgery@163.comBackground: This study focuses on the role of SIRT1 in neuroinflammation caused by early brain injury (EBI) after subarachnoid hemorrhage (SAH), and explores its mechanism in mitophagy after SAH.Methods: C57BL/6J mice and primary microglia SAH in vivo and in vitro models were constructed to explore the expression level of SIRT1 in neuroinflammation after SAH. Subsequently, the brain edema content, blood-brain barrier (BBB) damage and neurological function scores of the mice were observed after using the SIRT1 inhibitor EX-527. q-PCR and Western blot were used to detect relevant genes and proteins, and enzyme-linked immunosorbent assay (ELISA) was used to detect the levels of IL-6, IL-1β, and TNF-α inflammatory factors. Immunofluorescence staining was used to observe the positive level of SIRT1 and the degree of mitochondria-lysosome fusion, and transmission electron microscopy was used to observe mitochondrial damage and autophagosome levels.Results: In in vivo and in vitro experiments, we found that SIRT1 expression increased after SAH, and neurological deficits, brain edema, and blood-brain barrier damage after SAH were aggravated. Inhibiting SIRT1 further aggravates the aforementioned damage. In addition, EX-527 can also inhibit the level of mitophagy and aggravate neuroinflammation after SAH.Conclusion: Our results indicated that SIRT1 promotes mitophagy and alleviates neuroinflammation after SAH.Keywords: subarachnoid hemorrhage, SIRT1, mitophagy, early brain injury